Genotypes and Virulence Genes in Group B Streptococcus Isolated in the Maternity Hospital, Kuwait - Udo, Edet E. (Med Princ Pract, 2013)
OBJECTIVE: To characterize group B streptococcus (GBS) isolates obtained from patients at the Maternity Hospital in Kuwait for their genotypes and carriage of virulence genes. MATERIALS AND METHODS: A total of 154 GBS isolates were obtained from July 1 to October 31, 2007, from vaginal swabs (n = 95), urine (n = 46), blood (n = 4) and miscellaneous sources (n = 9). Genotypes were obtained by pulsed-field gel electrophoresis (PFGE), following digestion with SmaI or EagI restriction enzymes. PCR was used to screen for the carriage of virulence genes including: surface protein of group B streptococcus (spb1), secreted fibrinogen-binding protein (fbsB), C5a peptidase (scpB), laminin-binding protein (lmb), α− (bca) and β-subunits of the C protein (bac), resistance to protease immunity protein (rib), and phage-associated gene (pag); regulatory protein (dltR), and toxins CAMP factor (cfb), hyaluronidase (hylB) and superoxide dismutase (sodA). RESULTS: PFGE defined 14 genotypes differentiating isolates with the same serotypes into different genetic backgrounds. All isolates contained genes for virulence factors. However, cfb (99.4%), scpB (88.3%), lmb (88.3%), bca (57.8%), sodA (55.8%) and dltR (53.9%) were the common virulence genes. In total, 144 (90.3%) of the isolates contained 3 or more virulence genes. However, while cfb, lmb and scpB occurred in all genotypes, others occurred in some but not in all genotypes. CONCLUSIONS: GBS isolates obtained at the Maternity Hospital, Kuwait, belonged to diverse genetic backgrounds with the majority carrying multiple virulence genes.